The Effect of Employer Attractiveness, Social Media Use and Business Sustainability on The Intention to Apply For A Job To Start-Up Companies - Aprilia W Noviriani; Aman Wirakartakusumah (ARKA INSTITUTE, 2023)
Topics on employer attractiveness, social media use, and business sustainability on the intention to apply for a job especially to start-up companies. This research aims to analyze effect of employer attractiveness, social media use, and business sustainability on the intention to apply for a job especially to start-up companies in Greater Jakarta. The method research is multivariate data analysis model, including Partial Least Square Structural Equation Modelling (SEMPLS), which sample from 145 respondents in Greater Jakarta. The result shows that employer attractiveness has a positive and not significant effect on corporate reputation, social media use has a positive and significant effect on corporate reputation, business sustainability has a positive and significant effect on corporate reputation, and corporate reputation has a positive and significant effect on the intention to apply. For further research, academics can use the addition of other variables in subsequent studies that affect the corporate reputation variable and the intention to apply variable. In addition, research on future topics can also be studied in state-owned companies and government institutions. Another suggestion for further research is to use other sampling techniques, such as stratified random sampling or also use systematic random sampling so as to produce more varied respondents.